Epidemiology and outcomes of surgical site infections among pediatric liver transplant recipients. Issue 6 (21st September 2022) - Banach, David B.; Lopez‐Verdugo, Fidel; Sanchez‐Garcia, Jorge; Tran, Alexandria; Gomez‐Llerena, Adriana; Munoz‐Abraham, Armando Salim; Bertacco, Alessandra; Valentino, Pamela L.; Yoo, Peter; Dembry, Louise‐Marie; Mulligan, David C.; Ekong, Udeme D.; et al.
Abstract: Introduction: Surgical site infections (SSI) are a significant cause of morbidity in liver transplant recipients, and the current data in the pediatric population are limited. The goal of this study was to identify the incidence, classification, risk factors, and outcomes of SSIs among children undergoing liver transplantation (LT). Methods: A single‐center, retrospective descriptive analysis was performed of patients age ≤18 years undergoing LT between September 2007 and April 2017. SSI identified within the first 30 days were analyzed. Primary endpoints included incidence, classification, risk factors, and outcomes associated with SSIs. Results: We included 86 patients, eight patients (9.3%) developed SSIs. Among segmental grafts (SG) recipients, 7/61 (11.4%) developed SSI. Among whole grafts recipients, 1/25 (4%) developed SSI. SSIs were associated with the presence of biliary complications (35% vs. 3%, p < .01; odds ratios 24, 95% CI: 3.41‐487.37, p<.01). There were no differences in long term graft or patient survival associated with SSI. Patients who developed SSI were more likely to undergo reoperation (50% vs. 16.7%, p = .045) and had an increased total number of hospital days in the first 60 days post‐transplant (30.5 vs. 12.5 days, p = .001). Conclusions: SSIs after pediatric LT was less frequent than what has been previously reported in literature. SSIs were associated with the presence of biliary complications without an increase in mortality. SG had an increased rate of biliary complications without an association to SSIs but, considering its positive impact on organ shortage barriers, should not be a deterrent to the utilization of SGs. Abstract : Graphical Abstract